Spatio-temporal diffusion of solar thermal systems in Germany: A spatial panel data analysis - Jan Paul Baginski (University of Duisburg-Essen, House of Energy Markets & Finance, 2019)
Solar thermal roof-top installations offer the potential to meet an important share of residential water and space heating demand in Germany. These systems are subsidised with grants under the so-called market incentive program. The political goal is to encourage the adoption of renewable energy and to reduce CO2-emissions in the heating market in view of a low-carbon building stock. Solar thermal adoption levels are currently rather low after a high period in 2008 and 2009. Also, solar thermal adoption rates distinctly vary between regions. This paper tries to disentangle influences governing regional and temporal differences in residential solar thermal uptake. Spatial panel regression models are estimated to capture spatial interactions, while controlling for potential adoption determinants, including economic considerations, household characteristics and climatic suitability. The panel data contain observations for over 1 million solar thermal installations across 402 German regions covering the period from 2001 to 2015. Results indicate that differences in profitability influence the spatial and temporal patterns of solar thermal uptake. Regional diffusion is mainly driven by solar radiation. The development of fossil fuel prices is accountable for different adoption rates over time. New constructions do not seem to foster solar thermal use, indicating that solar heating is easily applied to existing houses. Larger households are more inclined to use solar heating, given that they use more efficiently solar generated heat. Results also show that spatial dependence drives the diffusion of solar thermal systems. These findings imply that there is potential for new policies and business models to increase the geographic and social diversification of solar thermal adoption.
Keywords: C23; D12; Q28; Q42; 330; solar energy; domestic solar thermal heating; spatial econometrics; panel data